New species, taxonomic changes and newly recorded species of Webbia Hopkins, ambrosia beetles from Thailand and neighbouring countries (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Sittichaya, Wisut; Smith, Sarah M.; Beaver, Roger A. (Zootaxa, 2023)
Four new species, Webbia aculeata Sittichaya, Smith & Beaver sp. nov., Webbia granulosa Sittichaya, Smith & Beaver sp. nov., Webbia planicauda Beaver, Sittichaya & Smith sp. nov., and Webbia spinosulcata Sittichaya, Smith & Beaver sp. nov., are described. Arixyleborus dissimilis (Eggers, 1923), and Arixyleborus orbiculatus (Eggers, 1923) are transferred to Webbia. Two new synonyms and a new combination are proposed: Webbia dissimilis (Eggers, 1923) comb. nov. (=Webbia costulatula Schedl, 1953 syn. nov.); Webbia hatanakai Browne, 1986 (=Webbia turbinata Maiti & Saha, 1986 syn. nov.). A lectotype is designated for Webbia orbiculata (Eggers, 1923) comb. res.. Three species, Webbia bituberculata (Browne, 1977), Webbia subuculae (Browne, 1962), and Webbia suturalis Browne, 1955 are recorded in Thailand for the first time. With the inclusion of the Webbia species described and recorded herein, the diversity of Webbia is increased to 41 species. A key is given to the 16 species recorded from Thailand.